Synthesis of Symmetrically Functionalized Oligo(het)arylenes Containing Phenylene, Thiophene, Benzthiophene, Furan, Benzofuran, Pyridine, and/or Pyrimidine Groups - Osadnik, Andreas; Lützen, Arne (Synthesis, 2014)
Rod-like oligomers consisting of thiophene and phenylene rings have proven to be highly interesting building blocks for the preparation of self-assembled, well-defined nanoaggregates via vapor deposition on solid supports. Changing the molecules’ chain length and substitution pattern allows to tailor the aggregates’ optical properties and morphologies. Thus, there is an ongoing demand for the synthesis of functionalized oligo(het)arylenes. Here, we describe an efficient and general approach for a broad spectrum of such molecules using a Suzuki cross-coupling strategy as the key reaction step.
Keywords: π-conjugated oligomers; Suzuki cross-coupling; thiophenylphenylenes; p-oligophenylenes; oligothiophenes